Analisis Kadar Vitamin C Pada Buah Manggis Yang Diperjualbelikan Di Pasar Terong Kota Makassar - Hasbi Hasbi; Asnurbaety Dwiyana; Muhajirah Mustafa (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2017)
Mangosteen contains a lot of vitamin C. Not only is its beautiful fruit shape and delicious meat taste, mangosteen also has many health benefits, as in the skin part of this fruit there is an antioxidant called xanthone which functions as an antioxidant anti-inflammatory activity no wonder Mangosteen fruit is known as the fruit that has the highest antioxidant content in the world and there are still many benefits contained in this fruit that have great benefits for humans. This type of research is laboratory observation with a descriptive approach that aims to determine the content of vitamin C levels in the mangosteen fruit that is traded on the market in the Eggplant City of Makassar using a UV-Visibel spectrophotometer. From the results of the analysis of the levels of Vitamin C in the mangosteen fruit in the 10gr sample containing vitamin C, that is, 0.05909 mg / gr, and vitamin c needed by the male body 90 mg and perenpuang 75 mg per day. To consumers to consume mangosteen because it can meet the body's needs.